The influences of the Big Five personality traits on academic achievements: Chain mediating effect based on major identity and self-efficacy - Wang, Hui; Liu, Yuxia; Wang, Zhanying; Wang, Ting (Frontiers in Psychology, 2023)
This study mainly uses the data of undergraduates majoring in business in a university in China to study the degree and path of the influence of personality traits on academic performance of high school students majoring in specific majors. It is found that rigorous personality traits have a significant positive impact on the academic performance of business students, and this impact is mainly achieved through the intermediary role of students' self-efficacy; Rigorous personality traits will strengthen business students' professional identity and further strengthen their self-efficacy, but professional identity has no direct impact on academic performance.